The Effect of Diabetes Management Shared Care Clinic on Glycated Hemoglobin A1c Compliance and Self-Management Abilities in Patients with Type 2 Diabetes Mellitus - Tian Jiang; Chao Liu; Ping Jiang; Wenjun Cheng; Xiaohong Sun; Jing Yuan; Qiaoling Wang; Yanlei Wang; Shihui Hong; Haiyan Shen; Dongchun Zhu; Yi Zhang; et al. (International Journal of Clinical Practice)
Objective. We aim to evaluate the impact of diabetes management shared care clinic (DMSCC) on glycated hemoglobin A1c (HbA1c) compliance and self-management abilities in patients with type 2 diabetes mellitus (T2DM). Methods. This study was a prospective cohort study of patients with T2DM participating in the DMSCC. At baseline and after management, the HbA1c levels were measured, the HbA1c compliance rate were calculated, and the Summary of Diabetes Self-Care Activities-6 (SDSCA-6), Diabetes Empowerment Scale-DAWN Short Form (DES-DSF), and Problem Areas in Diabetes Scale—Five-item Short Form (PAID-5) were completed. These pre- and post-management data were compared. Results. A total of 124 eligible patients were enrolled. After the diabetes management of DMSCC, the average HbA1c decreased and the HbA1c compliance rate increased significantly (P < 0.01). SDSCA-6 showed significant improvement in physical activity, glycemic monitoring, smoking (P < 0.01), and taking medication (P < 0.05). DES-DSF suggested a greater willingness to try to effectively treat diabetes (P < 0.05). PAID-5 indicated significant improvement in diabetes-related emotional distress. Conclusion. DMSCC can help patients with T2DM reduce HbA1c, increase HbA1c compliance, improve diabetes self-management behaviors, empowerment, and diabetes-related emotional distress and serve as an effective exploration and practice of diabetes self-management education and support.